1979
DOI: 10.1002/jez.1402080202
|View full text |Cite
|
Sign up to set email alerts
|

Solute compatibility with enzyme function and structure: Rationales for the selection of osmotic agents and end‐products of anaerobic metabolism in marine invertebrates

Abstract: The major nitrogenous osmolytes present in the cells of marine invertebrates, notably the free amino acids glycine, alanine and proline, and trimethylamine oxide and betaine, are highly compatible with proper enzyme function and structure. These nitrogenous osmolytes display either non-perturbing or, in some cases, favorable effects on enzyme-substrate and enzyme-cofactor complex formation, catalytic velocity and protein structural stability. In contrast, inorganic salts (KCl and NaCl) and certain of the free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
104
0
4

Year Published

1980
1980
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(116 citation statements)
references
References 46 publications
8
104
0
4
Order By: Relevance
“…The role of glycine in the protection of sperm during freezing-thawing process still not clear but many authors explain a suspected role in protection, as free amino acids and quaternary nitrogen containing compounds retard thermal denaturation of enzymes or provide thermal protection or maintain enzyme structure and function [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…The role of glycine in the protection of sperm during freezing-thawing process still not clear but many authors explain a suspected role in protection, as free amino acids and quaternary nitrogen containing compounds retard thermal denaturation of enzymes or provide thermal protection or maintain enzyme structure and function [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic ions are typically used in response to short-term and rapid changes in external osmolarity, while organic osmolytes are utilized during long-term acclimation (Silva and Wright 1994). Compatible organic osmolytes have the advantage of not interacting with intracellular metabolism, whereas inorganic ions and certain amino acids can have strong perturbing effects on vital functions, such as cellular enzymatic reactions (Bowlus and Somero 1979). Thus, osmoconformers employ a variety of cellular regulatory mechanisms to maintain relatively constant concentrations of intracellular inorganic ions when external salinity fluctuates.…”
Section: Introductionmentioning
confidence: 99%
“…A similar lack of correlation has also been found for MgC12 (Arakawa et al, 1990). Furthermore, in their study of the effects of osmolytes on the thermal stability of RNaseA, Bowlus and Somero (1979) found that all of the intracellular solutes they tested stabilized RNaseA structure, except for ArgHC1, which decreased the transition temperature of the protein. Because ArgHCl and LysHCl have the potential to interact directly with proteins, e.g., by hydrogen bonding to peptide groups, it was proposed that the measured preferential interactions are a summation of the effects of the increase in surface tension and weak binding (Kita et al,1 994).…”
mentioning
confidence: 99%